2019
DOI: 10.1186/s12052-019-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Does knowledge of evolutionary biology change high school students’ attitudes about healthy eating?

Abstract: Background: Embedded in the emerging area of evolutionary medicine is the premise that evolutionary biology can serve a pedagogical function with widespread applications for education and outreach. Although great strides have been taken over the decades by the science education community to improve evolution education in general, the knowledge gulf or gap between advances in evolutionary medicine and public understanding through the educational system has widened at a rapid pace-and not without consequences fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…To our knowledge, there is a single study that explored how evolutionary mismatch education impacts intentions to change behavior. Sherry (2018) [ 29 ] found that a one-time brief introduction to evolutionary biology produced a shift in high school students’ perceptions of healthy eating and led to intended dietary changes. Although, actual behavior was not measured.…”
Section: Lifestyle Behavior Change Via An Evolutionary Mismatch Narramentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is a single study that explored how evolutionary mismatch education impacts intentions to change behavior. Sherry (2018) [ 29 ] found that a one-time brief introduction to evolutionary biology produced a shift in high school students’ perceptions of healthy eating and led to intended dietary changes. Although, actual behavior was not measured.…”
Section: Lifestyle Behavior Change Via An Evolutionary Mismatch Narramentioning
confidence: 99%
“…Although, actual behavior was not measured. Sherry (2018) [ 29 ] found that explaining nutrition in an evolutionary context was necessary to change students’ perceptions of healthy eating. Our hypothesis builds upon these encouraging results.…”
Section: Lifestyle Behavior Change Via An Evolutionary Mismatch Narramentioning
confidence: 99%
“…In the German framework for Sachunterricht, under the theme of health, we nd an example lesson in which students compare the lifestyle and healthy behavior of humans in the stone age with the lifestyle and healthy behavior of children in the modern world, with the aim to help students understand and develop healthy behaviors such as exercise and diet (GDSU, 2013, p.146). This lesson implicitly uses the concept of evolutionary mismatch as a teaching moment to motivate behavior change (see also Basile et al, 2021;Sherry, 2019). Evolutionary mismatch can be de ned as "a negative consequence that results from a trait that evolved in one environment being placed in another environment" (Lloyd et al, 2011).…”
Section: Connections To Social-emotional Learning Goalsmentioning
confidence: 99%
“…Because it is known that the main factors that cause adverse effects on a person's weight status are physical inactivity and unhealthy dietary habits [5], [8]. Although very good knowledge of general guidelines for healthy eating, the occurrence of differences in the actions carried out by each person is strongly influenced by the perception factors that are built up in their minds [9].…”
Section: Introductionmentioning
confidence: 99%